2010
DOI: 10.1158/0008-5472.can-09-3813
|View full text |Cite
|
Sign up to set email alerts
|

Autotaxin Promotes Cancer Invasion via the Lysophosphatidic Acid Receptor 4: Participation of the Cyclic AMP/EPAC/Rac1 Signaling Pathway in Invadopodia Formation

Abstract: The ability of cancer cells to invade and metastasize is the major cause of death in cancer patients. Autotaxin (ATX) is a secreted lysophospholipase whose level of expression within tumors correlates strongly with their aggressiveness and invasiveness. ATX is the major enzyme involved in the production of lysophosphatidic acid (LPA), a phospholipid that is known to act mostly through its three first characterized receptors (LPA 1 , LPA 2 , and LPA 3 ). Tumor cell invasion across tissue boundaries and metastas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
62
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 48 publications
8
62
0
2
Order By: Relevance
“…In that study, silencing the expression of Rac1 or Trio was also shown to promote an increase in invadopodia lifetime, without affecting invadopodia numbers (Moshfegh et al, 2014). Even though our results contradict those of Moshfegh and colleagues (2014), they are in agreement with several reports which show Rac1 is required for invadopodia and podosome formation in different cell lines (Furmaniak-Kazmierczak et al, 2007;Harper et al, 2010;Lin et al, 2014;Nascimento et al, 2011;Pignatelli et al, 2012;Wheeler et al, 2006). Moreover, our results show that silencing SGEF or RhoG affects both invadopodia numbers and lifetime, whereas silencing Trio has no significant effect on the number of cells that form invadopodia.…”
Section: Discussionsupporting
confidence: 89%
“…In that study, silencing the expression of Rac1 or Trio was also shown to promote an increase in invadopodia lifetime, without affecting invadopodia numbers (Moshfegh et al, 2014). Even though our results contradict those of Moshfegh and colleagues (2014), they are in agreement with several reports which show Rac1 is required for invadopodia and podosome formation in different cell lines (Furmaniak-Kazmierczak et al, 2007;Harper et al, 2010;Lin et al, 2014;Nascimento et al, 2011;Pignatelli et al, 2012;Wheeler et al, 2006). Moreover, our results show that silencing SGEF or RhoG affects both invadopodia numbers and lifetime, whereas silencing Trio has no significant effect on the number of cells that form invadopodia.…”
Section: Discussionsupporting
confidence: 89%
“…For the non-EDG LPA-receptors, LPAR4-6, information on their role in cancer is very limited and few studies exist. LPAR4 has shown both antimigratory [54,55] and proinvasive effects [56]. LPAR5 inhibited migration [29], and LPAR6 (synonymous to P2Y5) was thought to be procancerous [57].…”
Section: Erk1 Erk2mentioning
confidence: 99%
“…Autotaxin and LPA promote the expression of the extracellular matrix protein osteopontin which promotes migration (Zhang et al 2011). Autotaxin activates the small G-proteins cdc42 and Rac (Jung et al 2002;Hoelzinger et al 2008;Harper et al 2010) and focal adhesion kinase (Jung et al 2002), proteins which are key regulators of cell motility. More direct evidence comes from the observation that knockdown of autotaxin inhibits cell migration in several cancer types Gaetano et al 2009;Harper et al 2010) and over-expression of autotaxin increases motility Harper et al 2010).…”
Section: Complexity In Lpa Receptorsmentioning
confidence: 99%
“…Autotaxin activates the small G-proteins cdc42 and Rac (Jung et al 2002;Hoelzinger et al 2008;Harper et al 2010) and focal adhesion kinase (Jung et al 2002), proteins which are key regulators of cell motility. More direct evidence comes from the observation that knockdown of autotaxin inhibits cell migration in several cancer types Gaetano et al 2009;Harper et al 2010) and over-expression of autotaxin increases motility Harper et al 2010). Autotaxin regulates the formation of invadopodia (Harper et al 2010) and induces the expression of uPA ) and MMP3 (Haga et al 2009).…”
Section: Complexity In Lpa Receptorsmentioning
confidence: 99%
See 1 more Smart Citation